Z-scan determination of two-photon absorption in Ag nano-fluid prepared using y-radiation methods. - Shahriari, Esmaeil; Mat Yunus, Wan Mahmood; Naghavi, Kazem (INOE Publishing House, 2010)
In this work the two-photon absorption (TPA) coefficients of Ag nano-fluid was measured using Z-scan technique. The Ag nano-fluid sample was prepared at 4.71×10-3 M concentrations and was radiated at different doses of γ-radiation. The conventional single beam Z-scan method with open aperture technique was used to measure the nonlinear absorption coefficient. A CW laser operated at 532 nm wavelength with output power of 40 mW was employed as the excitation source. The nonlinear absorption coefficient obtained was 5.8×10-3, 4.5×10-3 and 3.2×10-3 cm/W. The TPA processes was confirmed by optical limiting experimental data for the same laser beam excitation. The results show that the particle size gives a significant effect to the TPA coefficient.